Measuring Patient Satisfaction from Attitude toward Complementary and Alternative Medicine (CAM) Moderated by Patient Religiosity - Lusy Asa Akhrani; Yeni Ardyaningrum (Bina Nusantara University, 2019)
This research aimed to determine whether religiosity was able to be a moderator and strengthen the role of attitudes on CAM (Complementary and Alternative Medicine) as the originator of patient satisfaction in ‘sangkal putung’ treatment. The research applied a quantitative method with accidental sampling technique. The number of research respondents was 90 people aged 18 to 67 years old who visited the ‘sangkal putung’ at least twice and conducted treatment in the last 10 years. The research instrument used was SACAM (Scale for Attitude towards CAM) with the reliability of 0,843, PSQ-18 (Patient Satisfaction Questionnaire-Short Form) with the reliability of 0,859, and the Religiosity Scale was modified and rearranged based on the dimensions of religiosity by Stark & Glock with the reliability of 0,929. The research indicates that religiosity has a significant effect to strengthen the role of attitudes toward CAM as the originator of the treatment satisfaction of ‘sangkal putung’ patients. It means that the higher patient’s religiosity, the higher role of attitude towards CAM as the originator of the treatment satisfaction of ‘sangkal putung’ patients. Around 32,1% of the attitudes role towards cam works as a source of patient satisfaction of ‘sangkal putung’ treatment.